A “turn-on” fluorescent microbead sensor for detecting nitric oxide - Yang LH (Dove Medical Press, 2014)
Lan-Hee Yang,1,2 Dong June Ahn,3 Eunhae Koo1 1Advanced Materials Convergence Division, Korea Institute of Ceramic Engineering and Technology, Seoul, Republic of Korea; 2Department of Biomicrosystem Technology, Korea University, Seoul, Republic of Korea; 3Departments of Biomicrosystem Technology, Chemical & Biological Engineering, KU-KIST Graduate School, Korea University, Seoul, Republic of Korea Abstract: Nitric oxide (NO) is a messenger molecule involved in numerous physical and pathological processes in biological systems. Therefore, the development of a highly sensitive material able to detect NO in vivo is a key step in treating cardiovascular and a number of types of cancer-related diseases, as well as neurological dysfunction. Here we describe the development of a fluorescent probe using microbeads to enhance the fluorescence signal. Microbeads are infused with the fluorophore, dansyl-piperazine (Ds-pip), and quenched when the fluorophore is coordinated with a rhodium (Rh)-complex, ie, Rh2(AcO-)4(Ds-pip). In contrast, they are able to fluoresce when the transition-metal complex is replaced by NO. To confirm the “on/off” mechanism for detecting NO, we investigated the structural molecular properties using the Fritz Haber Institute ab initio molecular simulations (FHI-AIMS) package. According to the binding energy calculation, NO molecules bind more strongly and rapidly with the Rh-core of the Rh-complex than with Ds-pip. This suggests that NO can bond strongly with the Rh-core and replace Ds-pip, even though Ds-pip is already near the Rh-core. However, the recovery process takes longer than the quenching process because the recovery process needs to overcome the energy barrier for formation of the transition state complex, ie, NO-(AcO-)4-(Ds-pip). Further, we confirm that the Rh-complex with the Ds-pip structure has too small an energy gap to give off visible light from the highest unoccupied molecular orbital/lowest unoccupied molecular orbital energy level. Keywords: nitric oxide, microbead, fluorescence, rhodium complex, ab initio molecular simulation